Определение силы линий d–f переходов в кристалле YAG:Ce3+ - Д. Г. Заргарян (ՀՀ ԳԱԱ հրատ.)
Теоретически исследованы спектроскопические свойства кристалла YAG:Ce3+, обусловленные d–f переходами ионов Ce3+. В приближении среднего кристаллического поля определены энергии штарковских состояний 5d1 электронной конфигурации иона Ce3+ и построены соответствующие волновые функции. The theoretical study of the spectroscopic properties induced by d–f transitions in YAG:Ce3+crystal is carried out. In the framework of the mean-field approximation for crystal field the Stark states energies of 5d1 excited electronic configuration of Ge3+ ion are determined, as well as the wave functions of the corresponding Stark states are constructed.
Keywords: Physics; Science; Optics; Light